How blockchain technology can protect digital copyright in China, referring to the practice in Europe and the United States - Li, Bojun (My University, 2020)
This thesis focuses on how blockchain technology can be used to promote the development of the digital copyright industry in China. In the current information society, the digital copyright is suffering from infringement. The emergency of blockchain technology, with the characters of decentralization, disintermediation, immutability and traceability, can establish an open and transparent digital copyright management system, protecting the digital copyright in the aspects of copyright registration, transaction and protection. This thesis mainly uses doctrinal analysis and comparative analysis methods. The thesis analyzes the technological theory of the blockchain applications to the digital copyright protection, and compares the innovative practice of different digital copyright companies in China, European and American. Besides, the thesis also analyzes the judicial practice of blockchain technology in China. It can be concluded that the blockchain technology is able to provide a transparent and safe guarantee mechanism for the digital copyright industry, simplifying copyright registration; establishing a new profit and incentive model centered on the digital copyright owner; facilitating the legal process of the digital copyright protection. However, as a new technology, blockchain technology cannot solve all the digital copyright problems. It is a highly energy-consuming technology, and it also has defects such as the absence of the right to erasure and the digital transaction risks, etc.
Keywords: Blockchain technology, Digital copyright protection